THE EFFECT OF ARTEMIA BIOENCAPSULATION WITH SPIRULINA POWDER ON THE GROWTH PERFORMANCE OF DEPIK FRY (Rasbora tawarensis): PENGARUH ARTEMIA BIOENKAPSULASI DENGAN BUBUK SPIRULINA TERHADAP KINERJA PERTUMBUHAN BENIH IKAN DEPIK (Rasbora tawarensis) - Siti Komariyah; Purnawati Purnawati; Iwan Hasri; Andika Putriningtias (Fakultas Perikanan dan Ilmu Kelautan, IPB University, 2026)
The depik (Rasbora tawarensis) is one of the leading fishery commodities in Central Aceh Regency and is endemic to Laut Tawar Lake. Due to overfishing and environmental degradation, the depik is now endangered, necessitating domestication. The success of the domestication stage is influenced by providing feed that meets the fish's needs, such as Artemia encapsulated with spirulina to enhance the nutritional quality of the Artemia. This study aims to evaluate the effect. of spirulina dosage as an Artemia enrichment material on the growth performance of depik. The applied research design was a completely randomized design with four treatments replicated four times. The treatments included Artemia without bioencapsulation (Treatment 1/P1), Artemia bioencapsulation with 0.5 g of spirulina powder per liter of water (Treatment 2/P2), Artemia bioencapsulation with 1 g of spirulina powder per liter of water (Treatment 3/P3), and Artemia bioencapsulation with 2 g of spirulina powder per liter of water (Treatment 4/P4). The parameters observed were absolute length growth (ALG), absolute weight growth (AWG), specific growth rate (SGR), and survival rate. Based on the ANOVA test, different doses of spirulina had a significant effect (P < 0.05) on the growth and survival of depik fry. The higher the dose given, the higher the growth and survival performance produced. Based on the Duncan test, the best treatment was shown in Treatment 4, namely the provision of bioencapsulated Artemia with 2 g of spirulina powder as feed for the depik fry.